Anti-CD73 antibody activates human B cells, enhances humoral responses and induces redistribution of B cells in patients with cancer. Issue 12 (5th December 2022) - Miller, Richard A; Luke, Jason John; Hu, Shenshen; Mahabhashyam, Suresh; Jones, William B; Marron, Thomas; Merchan, Jaime R; Hughes, Brett G M; Willingham, Stephen B
Abstract : Background: CD73 is widely expressed on immune cells playing a critical role in immunomodulatory functions including cell adhesion and migration, as a costimulatory molecule for T cells and in production of adenosine. The function of CD73 expressed on B cells has not been fully characterized. Mupadolimab is an anti-human CD73 antibody that activates B cells. We evaluated the characteristics of this antibody and its effects on immune cells in vitro and in vivo. Methods: Mupadolimab binding to CD73, inhibition of CD73 enzymatic activity, and effects on lymphocyte activation were evaluated in vitro by measuring changes in immunophenotype by flow cytometry. Cryogenic-transmission electron microscopy was used to determine epitope binding. Effects on human B cells in vivo were evaluated in immunodeficient NSG-SGM3 mice immunized with SARS-CoV-2 and influenza viral antigens. Safety and immune effects were evaluated in the completed dose escalation portion of a phase 1 trial conducted in patients with cancer. Results: Mupadolimab binds to a unique epitope on CD73 POS B cells resulting in their activation and differentiation through B cell receptor signaling pathways. Mupadolimab induces expression of CD69, CD83, CD86 and MHC class II on B cells along with morphological transformation into plasmablasts and expression of CD27, CD38 and CD138. These effects are independent of adenosine. Mupadolimab binds to the N-terminal of CD73 in the closed position and competitively inhibits substrate binding. Mupadolimab enhanced antigen specific antibody response to SARS-CoV-2 spike protein and influenza hemagglutinin in humanized mouse models. Mupadolimab was evaluated as a monotherapy in a phase 1 trial (NCT03454451 ) in 34 patients with advanced cancer and demonstrated binding to CD73 POS circulating cells and transient reduction in the number of B cells, with return of CD73 NEG B cells with memory phenotype. No dose-limiting toxicities or changes in serum immunoglobulins were seen. Conclusions: Mupadolimab activates B cells and stimulates the production of antigen specific antibodies. The effects in patients with cancer suggest that activated, CD69 POS B cells redistribute to lymphoid tissues. Minor tumor regression was observed in several patients. These results support further investigation of mupadolimab as an immunotherapy for cancer and its potential use as a vaccine adjuvant. Trial registration number: NCT03454451 .